Modified Reverse Salam Product as an Innovative alternative for mobilizing fixed deposits in Jurisdictions with Limited Shariah Compliant Investment Avenues to Promote Financial Inclusion - Aishath Muneeza (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2019)
Financial inclusion is a mian concern of the contemperory global financial landscape. It is a universal concern that needs adequate and effective solutions. Islamic financial arean is no exception to this. With the fintech solutions available in the market today, innovative ways to provide financial inclusion is needed. However, the most critical challenge in the arena is caused due to limited availability of shariah compliant investment avenues in some of the jurisdictions of the world where Islamic banking and finance has not yet fully taken-off. The main objective of this research is to introduce a universally accepted mechanism using salam, one of the most least used Islamic finance contract in commercial Islamic banking for mobilising fixed deposits which will be ideal to be used in jurisdictions with limited shariah compliant avenues. This is a legal exploratory research that aims to provide an adequate and effective product for the jurisdictions that aspires to have sophisticated fixed return guranteed investment products structured in a shariah compliant manner. Simultaneously, the proposed product in this research will serve the less previlaged community of the society whose commodities can be used as underlying asset in structuring the product. However, this social impact of the product will differ depending on the jurisdiction in which it is applied and the decision of the financial institution in which the product is offered as it is there discretionary power to choose the underlying commodity used in the transaction. Fintech can also be fused with the suggested product and as such, the product can be easily used by the population in physically remote locations in a convenient manner. It is anticipated that this research will assist the jurisdictions in the world with limited shariah compliant investment products to introduce a new product that will be adequate to fulfill the needs of the customers.